2015
DOI: 10.1021/ar500359m
|View full text |Cite
|
Sign up to set email alerts
|

Flow Chemistry: Intelligent Processing of Gas–Liquid Transformations Using a Tube-in-Tube Reactor

Abstract: CONSPECTUS: The previous decade has witnessed the expeditious uptake of flow chemistry techniques in modern synthesis laboratories, and flow-based chemistry is poised to significantly impact our approach to chemical preparation. The advantages of moving from classical batch synthesis to flow mode, in order to address the limitations of traditional approaches, particularly within the context of organic synthesis are now well established. Flow chemistry methodology has led to measurable improvements in safety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
186
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(192 citation statements)
references
References 54 publications
1
186
0
5
Order By: Relevance
“…146,147 The inner capillary functions as a semipermeable membrane (Teflon AF-2400) and allows gas diffusion from the gas channel to the liquid channel. Recently, Gavriilidis et al demonstrated the use of this reactor for the solvent-free aerobic heterogeneous oxidation of benzyl alcohol.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
“…146,147 The inner capillary functions as a semipermeable membrane (Teflon AF-2400) and allows gas diffusion from the gas channel to the liquid channel. Recently, Gavriilidis et al demonstrated the use of this reactor for the solvent-free aerobic heterogeneous oxidation of benzyl alcohol.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
“…Gas-liquid chemical reactions include a broad range of highly relevant chemistries such as halogenation, oxidation, and hydrogenation, which are of great importance for fine chemical and pharmaceutical industries [1][2][3][4][5][6][7]. Gaseous reagents are prone to be atom economic [8]; however, they are often used in large stoichiometric excess because of insufficient interfacial mixing [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the so called tubein-tube reactor developed by Ley and coworkers has gained significant attention since its first application in 2010 [22]. In principal, this device consists of a gas-permeable Teflon AF-2400 membrane tubing (inner tube) that is fixed within larger impermeable tubing (outer tube).…”
Section: Technological Aspectsmentioning
confidence: 99%